New evidence for the medieval material culture of Chalcis (Negroponte): pottery, coins and coin containers (13th-14th centuries) - Skartsis, S; Vaxevanis, G; Baker, J (National Hellenic Research Foundation, National and Kapodistrian University of Athens, 2021)
This paper is a preliminary study of five refuse pits excavated in Chalcis (Euboea, Greece), which included large amounts of pottery, 54 diagnostic coins and more than 35 ceramic moneyboxes of the Lombard/Venetian period. The coins relate to certain instances in the history of Chalcis (and in fact of south-central Greece in general) and include a hoard of 37 rare coins of William of Villehardouin. The pottery reflects the economic and commercial growth of the city, the vitality of its ceramic workshops, as well as the availability to the local consumers of wares of various origins, qualities and values.